Morphology Effects of Ferrierite on Bifunctional Cu-ZnO-Al2O3/Ferrierite for Direct Syngas Conversion to Dimethyl Ether - Jung, Hyun Seung; Zafar, Faisal; Wang, Xu; Nguyen, Thi Xuan; Hong, Chae Hwan; Hur, Young Gul; Choung, Jin Woo; Park, Myung June; Bae, Jong Wook (ACS Catalysis, 2021)
Different roles of the solid-acid ferrierite zeolite (FER) morphology on the bifunctional Cu-ZnO-Al2O3(CZA)-incorporated FER were investigated for the one-step conversion of syngas to dimethyl ether by using three different FERs such as needle-like nanosheet, post-treated mesoporous, and commercial plate-like FERs having a similar Si/Al molar ratio of ∼10. The coprecipitated CZA nanoparticles on these FERs revealed significantly different catalytic activities and stabilities due to different dispersions of Cu nanoparticles with oxidation states as well as hydrophobicity of the FERs. Among them, the needle-like nanosheet FER incorporated with CZA (CZA/NSFER) showed the highest dispersion of Cu nanoparticles with homogeneous size distributions resulted in showing its higher thermal stability with less aggregations. The higher surface hydrophobicity was mainly responsible for the highly dispersed Cu-incorporated ZnO nanoparticles with less formation of CuAl2O4 phases on the CZA/NSFER by showing an enhanced catalytic activity and stability. The CZA/NSFER having a larger surface area of 142 m2/g showed more hydrophobic properties by showing much easier mass-transfer natures on the nanosheet FER surfaces. The superior catalytic activity on the CZA/NSFER with a reasonable activation energy of 62.6 kJ/mol was also attributed to the well-dispersed Cu crystallites on more hydrophobic Cu-ZnO-Al2O3 matrices on the mesoporous nanosheet NSFER surfaces.
Keywords: Bi-functional; Cu-ZnO-al2O3-incorporated ferrierite; Cu/ZnO/Al; Dimethyl ether synthesis; Ferrierite; Mesoporous; Morphology of ferrierite; Needle-like; One-step dimethyl ether synthesis; Cu-ZnO-Al2O3(CZA)-incorporated FER; hydrophobicity; morphology of ferrierite (FER); one-step dimethyl ether (DME) synthesis; synthesis gas